Constructing “constant-holistical shadow” space for universities in Guangzhou under the various roads orientation - Guohui, Luo; Nik Ibrahim, Nik Lukman; Kaiyi, Cui; Ziping, Gong; Lijun, Huang; Huaqing, Huang; Zhiyun, Wang; Wenjing, Luo (National University of Malaysia, 2025)
The university campus in Guangzhou city, China, are heavily exposed to the sun in the summer, and it is essential to construct a Constant-holistical Shadow (CHS) space that allows university teachers and students to remain in the shadow during their outdoor activities within a certain range of time and during the entire activity period. In this paper, based on the date period in need of shadow for the outdoor activities of university teachers and students in Guangzhou, the CHS spaces under 4 typical orientations, east-west, south-north, southeast-northwest, and northeast-southwest, were simulated by Autodesk Ecotect Analysis. The correlation between the objects blocking the sunlight (sunlight-blockers) and the simulation results is analyzed, to explore the construction and design method of CHS space under the difference of the orientations, and to form a process of designing CHS space that can be applied to different orientations of the building environment. Finally, the feasibility and scientific validity of these methods are simulated and verified step by step using a campus environment in a university in Guangzhou as an example, hoping to provide reference ideas and directions for the planning and design of universities in Guangzhou and its similar latitudes, as well as for the design of buildings and their renovation.